The impact of groupware and CSCW on group collaboration : an overview of success factors in CSCW - Nabben, Bastiaan (My University, 2019)
Organizations continuously explore new ways of supporting group collaboration. Group dynamics changed the moment organizations started to operate globally. Groups started to collaborate from different locations, and this caused the emergence of virtual teams and agile work. Microsoft is one of the companies that promises to support this new way of group collaboration. Organizations need new systems that connect distributed teams around the world. Groupware are computer-based systems that support groups of participants to achieve a common task in a shared environment. The focus of groupware is mainly on how the technology supports group collaboration. However, the technology alone is not interesting enough to be researched. The success of group collaboration is dependent on many more variables besides technology. Computersupported cooperative work (CSCW) is a research area that discusses the intersection between collaborative group behavior and computer-based technologies. It focusses on group behavior, group interaction, the work environment, and how computer-based systems can support those aspects. Even though CSCW was developed in the 1980s, it is still relevant today. The main research question of this paper is to find success factors of CSCW that support group collaboration. To answer the research question, literature is being reviewed, groupware is measured in use cases and interviews are conducted with Microsoft employees specialized in group collaboration systems. Results show that to support group collaboration, organizations should focus on active and dynamic participation of group members. Distributed organizations pulled groups apart and Passive group meetings in conference rooms are outdated and discourage collaboration. In addition, organizations must provide proper groupware to support common ground, grounding and group interaction.
Keywords: Groupware, CSCW, Common ground, Grounding, Group collaboration